Nanotechnology-Driven Therapeutic Innovations in Neurodegenerative Disorders: A Focus on Alzheimer's and Parkinson's Disease - Antea Krsek; Lara Baticic (MDPI AG, 2024)
Neurodegenerative disorders entail a progressive loss of neurons in cerebral and peripheral tissues, coupled with the aggregation of proteins exhibiting altered physicochemical properties. Crucial to these conditions is the gradual degradation of the central nervous system, manifesting as impairments in mobility, aberrant behaviors, and cognitive deficits. Mechanisms such as proteotoxic stress, neuroinflammation, oxidative stress, and programmed cell death contribute to the ongoing dysfunction and demise of neurons. Presently, neurodegenerative diseases lack definitive cures, and available therapies primarily offer palliative relief. The integration of nanotechnology into medical practices has significantly augmented both treatment efficacy and diagnostic capabilities. Nanoparticles, capable of traversing the blood-brain barrier, hold considerable potential for diagnosing and treating brain pathologies. By combining gene therapy with nanotechnology, the therapeutic effectiveness against neurodegenerative diseases can be substantially enhanced. Recent advancements in nano-biomaterial-based methodologies have fortified existing approaches to neural stem cell (NSC) differentiation therapies. NSC-targeting technologies offer a promising, potentially safe method for treating neurodegenerative diseases. This review endeavors to summarize current insights and perspectives on nanotechnology-driven therapeutic innovations in neurodegenerative disorders, with a particular emphasis on Alzheimer's and Parkinson's disease.